Strategi Pemasaran Digital : Membangun Awareness Green Environment Reduce, Reuse, Recyle Produk Komunitas Sangkar Semut - Muhammad Ilham Aji Faturahman; Bisma Widywan; Joni Haryanto; Indah Wahyu Maesarini (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
The problem faced by Sanggar Karya Seni Muda Taruna (Sangkar Semut) is the lack of innovation in using digital marketing to build awareness and to promote 3R (Reduce, Reuse, Recycle) of used goods. The purpose of this activity is to empower the Sangkar Semut community by digital marketing training especially the techniques in copywriting and capturing photos or videos to be posted in social media. The methods used in this training are with lectures, discussions, practices, and evaluations through observations, interviews, and questionnaires. The results of the activity show that there is an understanding from participants the importance of copywriting and good photoshots before being displayed on social media. Future activities such as creating content and steps to sell in marketspace are needed.